Seismic hazard assessment of Peninsular Malaysia based on new ground-motion prediction equations for subduction earthquakes - Shoushtari, Abdollah Vaez (2016)
On the basis of regional economic growth, most cities in Southeast Asia have seen rapid development over the past forty years. In general, seismic design has not been taken into account in Southeast Asia regions with low to moderate seismicity, as these areas have not experienced disaster caused by earthquakes. Peninsular Malaysia is an example of these regions. Although the main cities of this region are located in a low seismicity area, they may be vulnerable to distant earthquakes generated by active seismic sources located more than 300 km along and off the west coast of Sumatra Island. Since 2007, several earthquakes due to the local faults within the Peninsular Malaysia region with the maximum moment magnitude (Mmax) of 4.4 have occurred. Even though the local earthquakes were small in size, the epicenters were as close as 20 km to Kuala Lumpur, which could have remarkable effects on seismic hazard of the region. After understanding this fact that Peninsular Malaysia could be affected by either the large magnitude, distant Sumatran earthquakes or the local earthquakes, an appropriate seismic hazard maps and a set of desirable elastic response spectral acceleration for seismic design purposes would be required. Despite the earlier seismic hazard studies for this region, which were proposed based on only the far-field Sumatran earthquakes, this study has presented new maps and elastic response spectra using the combination of the local and Sumatran seismic sources. Ground-Motion Prediction Equations (GMPEs) are the main inputs in any seismic hazard assessment. This study has attempted first to derive new empirical spectral GMPEs for distant subduction earthquakes (the both interface and intraslab events). The proposed GMPEs are for peak ground acceleration (PGA), peak ground velocity, and 5% damped pseudo-acceleration for four site classes (i.e., National Earthquake Hazards Reduction Program (NEHRP) site class B, C, D, and E, corresponding to rock, stiff soil, medium soil, and soft soil site conditions). The response spectra database has been compiled from hundreds of groundmotion recordings from subduction earthquakes of moment magnitude (M) 5.0 to 9.1, hypocentral distance (Rhyp) of 120 to 1300 km and M 5.0 to 7.7, Rhyp 120 to 1400 km for interface and intraslab events, respectively. The probabilistic seismic hazard maps for PGA are presented over a 12.5 km grid for 10% and 2% Probabilities of Exceedance (PE) in 50 years corresponding to 475 and 2,475 years return periods, respectively. The proposed new hazard maps give the expected ground motions based on the extended earthquake catalogue, consideration of the both Sumatran and local seismic sources, upgraded seismic source parameters, and more compatible GMPEs. The maximum estimated PGAs on rock site condition across the Peninsular Malaysia region for 10% and 2% PE in 50-year are 11 %g and 20 %g, respectively. In final, the horizontal elastic and design acceleration response spectra following the principles of Eurocode 8, on four soil site conditions with soil factors of 1, 1.45, 2, and 2.35 for rock, stiff soil, medium soil, and soft soil ground types, respectively, have been presented for the Peninsular Malaysia region based on the computed uniform hazard spectra with 475 and 2,475 years return period.